Inclusive or exclusive : heritage and cultural tourism in post-apartheid South Africa - voberholzer@nwpg.gov.za (University of Pretoria, 2013)
Dissertation (MHCS (Heritage and Cultural Studies))--University of Pretoria, 2012.